2013
DOI: 10.1103/physreve.87.022803
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-induced resonance in the response to social norms

Abstract: In this paper we focus on diversity-induced resonance, which was recently found in bistable, excitable and other physical systems. We study the appearance of this phenomenon in a purely economic model of cooperating and defecting agents. Agent's contribution to a public good is seen as a social norm. So defecting agents face a social pressure, which decreases if free-riding becomes widespread. In this model, diversity among agents naturally appears because of the different sensitivity towards the social norm. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 49 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…A similar approach to look at norms in a public-goods setup [149] showed the appearance of so called diversity-induced resonance in an agent based model. The model considers 'conditional cooperation', a concept similar to self reinforcing dynamics, where the willingness of a user to follow a norm increases with the mass of followers.…”
Section: Modelling Normsmentioning
confidence: 99%
“…A similar approach to look at norms in a public-goods setup [149] showed the appearance of so called diversity-induced resonance in an agent based model. The model considers 'conditional cooperation', a concept similar to self reinforcing dynamics, where the willingness of a user to follow a norm increases with the mass of followers.…”
Section: Modelling Normsmentioning
confidence: 99%
“…Numerous studies have documented the emergence of resonance effects, i.e. the amplification of global network oscillations due to diversity, for both bistable and excitable oscillator networks [45][46][47][48][49][50][51][52][53][54]. This effect has been named diversityinduced resonance [45] and constitutes an important phenomenon in the context of the present work, where it will be studied by choosing network configurations, topology and coupling relevant to realistic β-cell clusters.…”
Section: Introductionmentioning
confidence: 94%
“…A recent work [10], whose main results are summarized in the Appendix of this paper, has reported that groups composed of humans facing a social dilemma are posed near a critical regime: traditionally, the concept of criticality arises in statistical mechanics in the study of phase transitions, and identifies an equilibrium configuration of a system poised at the boundary between a disordered and an ordered phase (as for instance liquid and solid, ferromagnetic and paramagnetic, and so on) [11][12][13][14]. Evidence of critical behaviour has been detected also in animal societies, such as flock of birds [15], ant groups [16], or communities of macaques [17], but to our knowledge [10] is the first to attest signatures of criticality in human cooperative systems too.…”
Section: Introductionmentioning
confidence: 99%